2020
DOI: 10.3390/ijerph17030692
|View full text |Cite
|
Sign up to set email alerts
|

Parental Attachment, Adult-Child Romantic Attachment, and Marital Satisfaction: An Examination of Cultural Context in Taiwanese and Thai Heterosexual Couples

Abstract: Relationship dynamics between married couples can differ considerably, with varying impacts on relationship satisfaction. However, very limited research attention has been paid to how intergenerational attachment, relating to an individual’s perception of his/her own and that of his/her parents’ attachment, can affect marital dynamics within different cultural contexts. The current study examined associations between married heterosexual couples’ romantic attachment, perception of parental attachment, and mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
3
4
0
Order By: Relevance
“…According to the present findings, Gotman's communication skills play a mediating role in avoidance-insecure attachment and marital satisfaction relationships. This finding is consistent with those reported by Huang et al (20), Mirhashemi and Akbarimoghadam (21), Arefi and Mohsenzadeh (18), Timm, and Keiley (19), and Candel and Turliuc (3). Couples with the avoidance-attachment style find intimacy worthless and fail to trust in their spouses.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to the present findings, Gotman's communication skills play a mediating role in avoidance-insecure attachment and marital satisfaction relationships. This finding is consistent with those reported by Huang et al (20), Mirhashemi and Akbarimoghadam (21), Arefi and Mohsenzadeh (18), Timm, and Keiley (19), and Candel and Turliuc (3). Couples with the avoidance-attachment style find intimacy worthless and fail to trust in their spouses.…”
Section: Discussionsupporting
confidence: 93%
“…The present study documented that Gotman's communication skills play a mediating role in the relationship between anxiety attachment and organizational marital satisfaction. The findings are consistent with those reported by Candel and Turliuc (3), Mirhashemi and Akbarimoghadam ( 21), Azizi and Beyranvand (17), Chung (12), and Huang et al (20). Anxiously attached spouses frequently contact their spouse, leave messages constantly, and are anxious about where their spouse is and what he/she is doing (5).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the findings of the study, it can be summarized that the attachment styles of Malaysian couples are culturally based or, in other words, determined by culture. This finding aligned with a comprehensive review by Huang et al (2020) who compared the differences of attachment styles between 62 regions in Southeast Asia and East Asia which showed that attachment styles are different from one region to another. Additionally, secure romantic attachment style was also found as a normative form in most (79%) cultures examined but not in all cultures (Schmitt, et al, 2004), which proved that secure is not a common style in all regions.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, there is continued controversy over the debate of attachment theory. According to Huang et al (2020), the cross-cultural research in the area of adult romantic attachment is still limited although cultural beliefs might help to explain different patterns of romantic attachment. This is an area in which more research is urgently needed as most of the cross-cultural comparisons focused on infant–mother attachment (Cowan & Cowan, 2007).…”
Section: Romantic Attachment Stylesmentioning
confidence: 99%